PENGEMBANGAN E-MODUL BERBASIS LIVE WORKSHEET MATERI MENULIS PUISI SISWA KELAS IV SEKOLAH DASAR - Wati, Siti Fajar; Denna Delawanti Chrisyarani; Dwi Agus Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In learning Indonesian in elementary schools, teachers only use traditional and conventional teaching materials such as the use of PPT (power point). So that students easily get bored in the learning process in class. The purpose of this study was to determine the validity, practicality, and effectiveness of the development of E-Modules based on Live Worksheets for writing poetry for grade 4 elementary school students. This development research uses the Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data analysis in this study used qualitative and quantitative. Based on the results of the assessment of media experts, the percentage was 93.75%, material experts 95.45%, language experts 100%, from the three experts they got an average of 96.4% with the category